Penilaian Kinerja Pada Pembelajaran Maharah Al-Kalam Level 1 Di Kursus Bahasa Arab Al-Arobiya Surakarta - Joko Widodo; Muhammad Nanang Qosim (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2021)
Performance assesment is a form of assessment that requires students to practice the knowledge that has been learned in various contexts according to the desired criteria. Performance assessment is needed to measure students' ability in learning Arabic objectively. The competencies achieved by speaking skills learners are being able to converse in Arabic fluently and correctly. Aspects that are assessed in the speaking skills assessment include: 1) pronunciation, 2) grammar, 3) vocabulary, 4) fluency, 5) content of speech, 6) understanding. This research is a descriptive qualitative research and type of field research. The data collection technique used was direct observation, interviews and documentation. The performance assessment of Arabic speaking skills of students of the Al-Arobiya level 1 course is carried out in class. Practice Arabic for beginners at the venue by memorizing the lesson text and then pairing up dialogue. Assessment results vary; quite competent, competent and very competent.